Improving the efficiency of discharge summary completion by linking to preexisiting patient information databases. Issue 1 (16th May 2014) - Chan, Samuel; P Maurice, Andrew; W Pollard, Clifford; J Ayre, Stephen; L Walters, Darren; E Ward, Helen
Abstract: The discharge summary (DS) is a document that contains the diagnosis, comorbidities, procedures, complications, and future treatment plan for a particular patient after an inpatient hospital stay. The DS is completed by junior medical staff and is delivered to the general practitioner (GP). DS completion is time consuming and tedious, and DSs are usually not completed within the recommended time frame after a patient is discharged. Time spent completing DSs correlate to junior doctor overtime, which costs the hospital money in overtime pay. Information that is required in the DS is generally already entered into numerous electronic information systems in the hospital, including the "electronic patient journey board" which lists all the patients in a given ward with their clinical information. This information is constantly updated by all staff in the hospital. A program was developed that transferred this information directly into the patient DS. Ten junior doctors in two departments kept daily records for one week of the time spent compiling DSs, the time at work and the actual overtime claimed, before and after the introduction of the intervention. The mean (± SD) time for DS compilation per week reduced by 2.8 (± 2.4) hours from 10.0 (±3.5) hours (p<0.01) and the mean overtime worked per week reduced by 2.8 (± 3.1) hours from 8.5 (± 4.4) hours (p<0.05). The mean overtime claimed reduced by 1.8 (± 2.8) hours from 5.3 (± 5.4) hours per week (p<0.05), resulting in reduction in mean overtime payment of 114.95 from 290.57 per doctor, per week. Extrapolating to the 60 ward based junior doctors, the potential annual savings for the hospital budget are over 350, 000. Additionally, the number of DSs completed within 48 hours increased from 45% to 58%. In summary, the transfer of electronic data from the electronic patient journey board to the discharge summary program has yielded improvements in DS completion rates and overtime worked by medical staff, resulting in significant reduction in overtime costs.